2015
DOI: 10.4236/ajps.2015.62031
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Temperature and Nutrient Enrichment on Palatability of the Brown Alga Sargassum yezoense (Yamada) Yoshida & T. Konno

Abstract: Global warming is predicted to strengthen marine plant-herbivore interactions. However, little is known about the effect of temperature on palatability and the associated chemical composition of marine macroalgae. To study the effects of physiological stress caused by the warm water temperatures and nutrient-poor conditions that occur during summer, we cultured the brown alga Sargassum yezoense at three different temperatures (16˚C, 22˚C, and 28˚C) in both nutrient-enriched and non-enriched media. We then comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…Similarly, Poore et al () found no effect of increased temperature from 23 to 26°C on the phlorotannin content of Sargassum linearifolium (Turner) C. Agardh in a 14 days experiment. We previously reported that a wider temperature range had no effect on phlorotannin content in S. patens (10–30°C) and S. yesoense (16–28°C) across 8 and 9 days experiments (Endo et al , ). In the present 9 days experiment, we did not detect an effect of elevated temperature between 23 and 26°C on the phlorotannin content in E. bicyclis .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Poore et al () found no effect of increased temperature from 23 to 26°C on the phlorotannin content of Sargassum linearifolium (Turner) C. Agardh in a 14 days experiment. We previously reported that a wider temperature range had no effect on phlorotannin content in S. patens (10–30°C) and S. yesoense (16–28°C) across 8 and 9 days experiments (Endo et al , ). In the present 9 days experiment, we did not detect an effect of elevated temperature between 23 and 26°C on the phlorotannin content in E. bicyclis .…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, to avoid both the occurrence of diatom blooms and the utilization of GeO 2 , we used a 25% PESI medium (Tatewaki ), as opposed to a 100% medium, and limited the culture period to 9 days, based on our previous experience. While there is no information available on the optimal and critical nutrient levels for E. bicyclis juvenile sporophytes, significant nutrient enrichment effects of a 25% PESI medium on the growth of Undaria pinnatifida (Harvey) Suringar (Gao et al ) and on phlorotannin content in the brown algae Sargassum patens C. Agardh and S. yezoense (Yamada) Yoshida & T. Konno have been reported (Endo et al , ). Therefore, in the present study, a 25% PESI medium and non‐enriched sterile seawater were used to represent enriched and ambient nutrient conditions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All species are abundant canopy-forming algae in Tosa Bay 23 . Their depth distribution is between 1 and 10 m. Seaweed palatability may vary between populations in regional and latitudinal scales 17 probably because seawater nutrient conditions may affect palatability 36 . This study aimed to compare the differences in palatability among macroalgae species therefore all seaweeds were collected from the same location (Pacific Ocean side of the Yokonami Peninsula, central Tosa Bay).…”
Section: Methodsmentioning
confidence: 99%
“…In marine communities, the preference and performance of the herbivores often relate directly to the nutritional value of algae or some other autotrophs, which is driven mostly by the protein and nitrogen content [ 151 , 152 , 153 , 154 , 155 ]. For example, several studies on the high-value marine abalone (Haliotis asinine) suggested that their diverse preferences are primarily influenced by the protein and nitrogen content of macroalgae [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. Table 3 shows some examples of studies involving the interactions between marine autotrophs and herbivores based on the herbivore nutrient acquisition since the 2010s.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%
“…Living organisms require nitrogen to synthesize amino acids, the basic building blocks of protein that serve essential functions in virtually all biological processes [ 153 ]. Many previous studies have pointed out that low nitrogen consumption is associated with reduced food intake in generalist marine herbivores [ 39 , 148 , 160 , 161 , 162 , 163 ]. The study by Barile, Lapointe and Capo [ 156 ] on California sea hare ( Aplysia californica ) showed that this herbivorous gastropod preferred to feed on gracilarioid algae ( Gracilaria ferox ) with high levels of nitrogen.…”
Section: Does Nutrient Acquisition In Algae Determine the Feeding Pre...mentioning
confidence: 99%